The Analgesic Effects of a Bilateral Sternal Infusion of Ropivacaine After Cardiac Surgery. Issue 2 (1st March 2012) - Eljezi, Vedat; Dualé, Christian; Azarnoush, Kasra; Skrzypczak, Yvan; Sautou, Valérie; Pereira, Bruno; Tsokanis, Ianis; Schoeffler, Pierre
Abstract : Background and Objectives: The aim of this study was to assess the effects of a continuous postoperative administration of local anesthetic through 2 catheters placed deeply under fascia at the lateral edges of the sternum, close to the emergence of the intercostal nerves. We focused on pain during mobilization, as this aspect is likely to interact with postoperative morbidity. Methods: Forty adult patients scheduled for open heart surgery with sternotomy were included in this randomized, placebo-controlled, double-blind study. A continuous fixed-rate infusion of 4 mL/hr of 0.2% ropivacaine or normal saline was administered during the first 48 postoperative hrs. All patients received acetaminophen and self-administered morphine. The efficacy outcomes were as follows: pain score during standardized mobilization and at rest; morphine consumption; spirometry and arterial blood gases; postoperative rehabilitation criteria, and patient satisfaction. Total ropivacaine plasma level was monitored throughout the study. Results: Pain scores were lower in the ropivacaine group during mobilization ( P = 0.0004) and at rest ( P = 0.0006), but the analgesic effects were mostly apparent during the second day after surgery, with a 41% overall reduction in movement-evoked pain levels. The bilateral sternal block also reduced morphine consumption. It improved the patients' satisfaction and rehabilitation, but no effects were noted on respiratory outcomes. No major adverse effect due to the treatment occurred, but the ropivacaine plasma level was greater than 4 mg/L in 1 patient. Conclusions: This technique may find a role within the framework of multimodal analgesia after sternotomy, although further confirmatory studies are needed.